2001
DOI: 10.1103/physrevd.63.054003
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic dynamics of disoriented chiral condensate formation

Abstract: The dynamics of the pion field after a quench is studied in the framework of the linear sigma model. Our aim is to determine to what extent the amplified pion field resembles the disoriented chiral condensate ͑DCC͒ picture originally proposed in the early 1990s. We present the result of a computer experiment where, among other things, we study in detail the correlation between isospin orientations of the distinct modes of the field. We show that this correlation is absent. In a sense, the distinct modes behave… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…This question has been investigated in Ref. [97], where a detailed statistical analysis of the pion field configurations produced after a quench has been performed, with particular emphasis on their isospin structure. For this purpose, it is sufficient to consider the original model of Rajagopal and Wilczek [10], see subsection 2.2.1, which includes all the relevant physical features.…”
Section: The Unpolarized DCCmentioning
confidence: 99%
See 1 more Smart Citation
“…This question has been investigated in Ref. [97], where a detailed statistical analysis of the pion field configurations produced after a quench has been performed, with particular emphasis on their isospin structure. For this purpose, it is sufficient to consider the original model of Rajagopal and Wilczek [10], see subsection 2.2.1, which includes all the relevant physical features.…”
Section: The Unpolarized DCCmentioning
confidence: 99%
“…32 For a more detailed analysis, see Ref. [97]. wheren a (k) ≡n a (k, t f ) represent the averaged occupation numbers corresponding to the classical field configuration at the final time t f , see Eq.…”
Section: The Unpolarized DCCmentioning
confidence: 99%
“…For instance, the thermalization of an idealized form of color glass condensate [10] was studied by Bjoraker and Venugopalan by [11] solving the Landau transport equation. Serreau and Schiff also investigated the same topic in [12] where they used the relaxation time approximation to simplify the collision term in the Boltzmann equation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Serreau and Schiff [ 5] have studied the role of elastic processes in kinetic equilibration using minijets as well as color glass condensate as initial conditions and found that in all cases elastic interactions alone cannot drive the system rapidly to kinetic equilibrium. It is interesting to see whether the situation changes when the inelastic gg ↔ ggg processes are included.…”
Section: Introductionmentioning
confidence: 99%